2023
DOI: 10.1073/pnas.2309047120
|View full text |Cite
|
Sign up to set email alerts
|

PARP7-mediated ADP-ribosylation of FRA1 promotes cancer cell growth by repressing IRF1- and IRF3-dependent apoptosis

Patrick Manetsch,
Flurina Böhi,
Kathrin Nowak
et al.

Abstract: PARP7 was reported to promote tumor growth in a cell-autonomous manner and by repressing the antitumor immune response. Nevertheless, the molecular mechanism of how PARP7-mediated ADP-ribosylation exerts these effects in cancer cells remains elusive. Here, we identified PARP7 as a nuclear and cysteine-specific mono-ADP-ribosyltransferase that modifies targets critical for regulating transcription, including the AP-1 transcription factor FRA1. Loss of FRA1 ADP-ribosylation via PARP7 inhibition by RBN-2397 or mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The remaining modifications are in intrinsically disordered regions near the ZZ-type zinc finger (ZZ domain) and the nuclear localization/export sequence (NLS/NES). These p62-specific cysteine residues were also identified in the NSCLC cell line NCI-H1975 58 under unstimulated conditions, supporting that these cells are in a viral mimicry primed state 59 .…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…The remaining modifications are in intrinsically disordered regions near the ZZ-type zinc finger (ZZ domain) and the nuclear localization/export sequence (NLS/NES). These p62-specific cysteine residues were also identified in the NSCLC cell line NCI-H1975 58 under unstimulated conditions, supporting that these cells are in a viral mimicry primed state 59 .…”
Section: Resultsmentioning
confidence: 58%
“…1B) in A549 cells due to p62's well-described functions in viral clearance 56,57 . In addition, a modification at C331 was identified in NCI-H1975 58 , which is located in the LC3 interaction region (LIR). The remaining modifications are in intrinsically disordered regions near the ZZ-type zinc finger (ZZ domain) and the nuclear localization/export sequence (NLS/NES).…”
Section: Sqstm1/p62 Is Mono-adp-ribosylated At Specific Cysteine Resi...mentioning
confidence: 99%
See 1 more Smart Citation
“…These results may in part be explained by the decrease in the expression of PARPBP and TIPARP in FK866-treated cells. These proteins have previously been associated with resistance to DNA damage and apoptosis, respectively [ 47 , 48 ]. Whilst we did not observe any significant changes in apoptosis with FK866 alone, others have shown that when NAMPT inhibitors are combined with TMZ, the ROS/JNK signalling pathway is activated, leading to significant increases in apoptosis in vitro [ 49 ].…”
Section: Discussionmentioning
confidence: 99%